Condition of the Cardiovascular System in Children with Chronic Pyelonephritis on the Background of Hyperuricemia (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Comparative clinical-laboratory and instrumental evaluation of 62 children with chronic pyelonephritis was carried out. It was revealed that the increase in the level of MC significantly influences the development and progression of the cardiovascular system disease, which was expressed in higher blood pressure level, statistically higher frequency of pathological changes at ECG, as well as EchoCG, which is expressed in higher frequency of left ventricular hypertrophy.